2017
DOI: 10.32677/ijch.2017.v04.i03.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total serum immunoglobulin E and absolute eosinophil count levels among asthmatic and non-asthmatic children

Abstract: Background: Immunoglobulin E (IgE) and associated cellular responses such as absolute eosinophil count (AEC) are responsible for allergic airway diseases. A hypersensitivity reaction initiated by immunological mechanisms, mediated by IgE antibodies, and eosinophils occur in allergic asthma. Objective: To compare the total serum IgE level and AEC levels among asthmatic and non-asthmatic children. Methods: The present study was conducted in the department of pediatrics and TB and Chest of a Medical College of No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
6
8
0
Order By: Relevance
“…In the present study, male to female ratio was 1.4: 1, which was similar to the study done by Uyan et al in which asthma was found to be significantly higher in boys than in girls (1.4:1). 7 In the present study, urban predominance was seen which was in accordance with the study by Srinivasa et al and Chaudhary et al 8,9 The present study observed 45.67 % of the cases with a family history of asthma similarly Stephanie J et al observed greater associations between childhood asthma and family history of asthma. 10 We found allergic rhinitis was common comorbid condition seen in asthmatic children as was observed by studies done by Bisaccioni et al and Sanja Dimitrijevic et al 11,12 In present study, 59% children belonged to low socioeconomic class, 31% children were from middle socio-economic class and 10% were from upper socioeconomic class.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, male to female ratio was 1.4: 1, which was similar to the study done by Uyan et al in which asthma was found to be significantly higher in boys than in girls (1.4:1). 7 In the present study, urban predominance was seen which was in accordance with the study by Srinivasa et al and Chaudhary et al 8,9 The present study observed 45.67 % of the cases with a family history of asthma similarly Stephanie J et al observed greater associations between childhood asthma and family history of asthma. 10 We found allergic rhinitis was common comorbid condition seen in asthmatic children as was observed by studies done by Bisaccioni et al and Sanja Dimitrijevic et al 11,12 In present study, 59% children belonged to low socioeconomic class, 31% children were from middle socio-economic class and 10% were from upper socioeconomic class.…”
Section: Discussionsupporting
confidence: 92%
“…16,17 The present study also revealed increased mean serum IgE levels (range: 247-1747 IU/ml) and correlated well with severity of asthma. These finding were consistent with studies done by Ching et al, Chandran et al and Chaudhary et al 18,19,9 In Thirunavukkarasu Sandeep et al study mean IgE levels ranged from 151.95 IU/ml in normal subjects to 1045.32 IU/ml in severe asthmatics and they also observed that IgE levels were increased as the severity of asthma was increased. 20 Limitations of present study were small population and it is not a case control study as the serum IgE level was an invasive, costly and time-consuming test.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been noted that the mean serum tIgE levels in children with asthma was significantly higher than those in normal controls (p value <0.001). [16][17][18][19] In this study serum tIgE levels were above the normal limit for age in 86.2% patients with asthma. Chandran et al, Chaudhary et al, and Lama et al, found raised serum tIgE levels in 75% ,71.4% and 63.3% of asthmatic children respectively.…”
Section: Discussionmentioning
confidence: 86%
“…Chandran et al, Chaudhary et al, and Lama et al, found raised serum tIgE levels in 75% ,71.4% and 63.3% of asthmatic children respectively. 11,16,18 There is a strong relationship between increased serum tIgE levels and asthma prevalence. 20 Authors noted an increase in the levels of serum tIgE as the severity of asthma increased and this was statistically significant.…”
Section: Discussionmentioning
confidence: 99%